2022
DOI: 10.1038/s41598-022-06600-1
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal activity of seaweed-synthesized silver nanoparticles and extracts against Meloidogyne incognita on tomato plants

Abstract: The purpose of this study was to test the nematicidal activity of extracts of two marine algae (Colpomenia sinuosa and Corallina mediterranea) and their synthesized silver nanoparticles against root-knot nematodes (Meloidogyne incognita) that infest tomato plants. Scanning electron microscopy (SEM) revealed that nanoparticles had aggregated into anisotropic Ag particles, and transmission electron microscopy (TEM) revealed that the particle sizes were less than 40 nm. Fourier Transform Infrared Spectroscopy (FT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…J2s invade roots, migrate to vascular tissues and form ‘root knots’ or ‘galls’ as well as develop special ‘giant feeding cells’, permanently affecting the nutrient and water uptake in their host [ 11 ]. Speedy population growth of M. incognita due to high female fecundity and completion of two or more life cycles in a single growing season, leads to declining crop yield and causing huge financial adversity to farmers worldwide [ 12 ]. The use of chemical based synthetic nematicides is still the primary managing technique against PPNs.…”
Section: Introductionmentioning
confidence: 99%
“…J2s invade roots, migrate to vascular tissues and form ‘root knots’ or ‘galls’ as well as develop special ‘giant feeding cells’, permanently affecting the nutrient and water uptake in their host [ 11 ]. Speedy population growth of M. incognita due to high female fecundity and completion of two or more life cycles in a single growing season, leads to declining crop yield and causing huge financial adversity to farmers worldwide [ 12 ]. The use of chemical based synthetic nematicides is still the primary managing technique against PPNs.…”
Section: Introductionmentioning
confidence: 99%
“…The use of optimum N fertilizer improves a variety of physiological and metabolic activities, including photosynthesis and nitrogen metabolism, which is a critical reducing factor in high cotton productivity and quality. As a result, one of the most essential ways to boost cotton output is to apply N fertilizer ( Boquet and Breitenbeck, 2000 ; Muhammad et al, 2019 ; Yousaf et al, 2021 ; Ghareeb et al, 2022 ). Many research has demonstrated that a sufficient amount of N nutrition may boost cotton dry matter and growth rate at all stages ( Luo et al, 2009 ; Fouda et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results proved that AgNPs had a positive influence on improving the vegetative growth, yield, and fruit quality of lemon ( C. limon L.). AgNPs are promising materials that have a good influence on the development of crops, particularly by improving the flowering rate, the proportion between root and shoot systems, the growth of seeds, and the formation and rigidity of roots ( Ma et al, 2011 ; Fouda et al, 2020a ; Dutta et al, 2022 ; Ghareeb et al, 2022 ; Mahajan et al, 2022 ). The application of NPs in the agricultural sector improved the resistance to diseases, increased the efficiency of plant elements uptake, pests’ control, raised the ecological pressures tolerance, and provided a processing and storage coefficient system to increase crop productivity ( Mousavi and Rezaei, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, their thorough use has led to severe problems similar to insecticide resistance in several stored product insects like Sitophilus species ( Fields and White, 2002 ; Ducom, 2012 ; Maletsema Alina, 2016 ; Pavlidi et al, 2018 ; Chelef et al, 2020 ). The other safe, effective, and eco-friendly methods are using alternative insecticides such as EOs and plant extracts to control insects’ stored products ( Koul and Walia, 2009 ; Mamun and Ahmed, 2011 ; Mackled et al, 2019 ; Mahomed et al, 2019 ; Mosa et al, 2021 ; Ghareeb et al, 2022 ). The activity of insecticides on different citrus species has been demonstrated in numerous studies ( El-Akhal et al, 2014 ; Abdelgaleil et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%